Plasmodium falciparum resistance and malaria presentation in children at Dongola specialist hospital: A prospective cohort study - Abdelbagi Elfadil Mousa; Hamoud Abdullah Alsamhan; Hafsa Elawd Mohamed Ahmed; Mohamed Abd Rhman Adris Abdallah; Osman Mohamed Elhadi Abdalla; Taroob Abdalwahab Abdalhameed; Hamed Alneel Albagir Ahmed; Sania Abdalla Shaddad; Abdlrahim Abdlahman Abdlhim; Hashim Ezeldin Ibrahim Salih; et al. (Journal of the Pakistan Medical Association, 2022)
Objective: To provide evidence about the susceptibility of anti-malarial drugs, and to identify the clinical features of the disease in children. Method: The prospective observational comparative study was conducted at the Dongola Specialist Hospital, Dunqulah, Sudan, from February 2016 to February 2017, and comprised children aged <16 years with bodyweight >5kg who had malaria. The subjects were enrolled into group 1, which received treatment based on physician’s discretion, and group 2, which received treatment in accordance with the national guideline. The follow-up was conducted on days 3, 7 and 14 to identify cases as early treatment failure, late treatment failure, or treatment success. Data were analysed in terms of frequencies and percentages using statistical analysis software R version 3.1.2. Results: Of the 120 children, 60(50%) were in each of the two groups. Overall, 63(52.5%) were aged 1-6 years, 66(55%) were males, and 42(35%) were exposed to malaria for the first time. Post-treatment test was negative for all 120(100%) the subjects in both the groups. showing no inter-group difference. Conclusion: Although resistance to combination therapy was not detected, it remains extremely important to remain vigilant for the emergence of resistance in the future. Key Words: Child, Drug resistance, Malaria, Sudan. Continue...